Challenges and Perspectives for Development of Banking Credit Infrastructure in Russia - Ezangina, Irina Alexandrovna; Evstratov, Alexander Vladimirovich; Jovanovic, Tamara Georgievna (International Journal of Economics and Financial Issues, 2016)
The purpose of this study is to demonstrate the role of modern credit infrastructure as the most important institutional component of the market of bank loans ensuring the development of credit relations, the minimization of credit risks and the creation of organizational, technological and legal environment in order to organize an effective system of bank lending. The main participants (credit bureaus, rating agencies, appraisals of borrowers of the company, banking associations, centres for market investigations, collection agencies, stock exchanges, lending agents, brokers, dealers, public institutions represented by the Bank of Russia and Federal State Statistics Service) are identified, the functional role of some of the most significant ones in Russia is defined. Preconditions for the development of the credit market infrastructure on a global scale are specified, the problem field of activity of the relevant Russian institutions is investigated. Several activities, related to the modernization and increased efficiency in their operations in Russia, are proposed. In particular, the content of reference projects on the establishment of the National Bureau of Credit Histories, the development of the national system of accreditation of credit rating agencies and the establishment of a comprehensive system of guarantee funds is updated. A conclusion about the need to strengthen the special status of the Bank of Russia as an organizer of monitoring of the credit market infrastructure and a single methodological centre is made. Keywords: credit market, credit market infrastructure, collection agency, credit rating agency, guarantee fund, JEL Classifications: G20, G21, L10, O16, E44.